STUDENTS’ PERCEPTION ON THE USE OF GOOGLE CLASSROOM IN LEARNING ENGLISH PROCESS - Husniah S; A. Muliati; Munir Munir (Universitas Negeri Makassar, 2022)
This study aims to describe students’ perceptions of the use of Google Classroom in the learning English process. The researchers applied qualitative methods to achieve the research objectives, the data collected in this research were in the form of interviews. The subjects of this study were students in the third grade of SMA NEGERI 2 BONE. The interview sample was 20 students, using voluntary sampling technique. In this study, researchers analyzed the data by understanding, compiling codes, looking for themes and drawing conclusions. Based on the results of the study, the researchers found that students' perceptions of the use of Google Classroom in learning process as a flexible, efficient, effective media and interaction between teacher and some of students continued smoothly learning process. Although, cheating is still common due to lack of control, but Google Classroom has features that can overcome this. Most of the students in this study agreed that Google Classroom were effective when used for Learning process.